2019
DOI: 10.1186/s12889-019-7544-0
|View full text |Cite
|
Sign up to set email alerts
|

Repeated high blood pressure at 6 and 11 years at the Pelotas 2004 birth cohort study

Abstract: Background We evaluated the prevalence and the factors associated with repeated high systolic (SBP) and diastolic blood pressure (DBP) at 6- and 11-year follow-ups of children from the Pelotas (Brazil) 2004 Birth Cohort. Methods All live births to mothers living in the urban area of Pelotas were enrolled in the cohort. Blood pressure (BP) values were transformed into Z-scores by sex, age, and height. High SBP and DBP were defined as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Numerous studies have assessed whether maternal GDM was a risk factor for offspring elevated BP, and our study is in line with those showed a positive association of GDM with childhood increased BP. 8,28 We found the HBP risks in non-GDM group was 12.2%, which was similar to a prevalence of 12.8% in 5381 Portuguese children and adolescents measured by single visit. 29 The HBP risks in GDM group was 17.4% (male: 22.6%, female: 12.9%), which was also comparable to Marion et al's study.…”
Section: Discussionsupporting
confidence: 78%
“…Numerous studies have assessed whether maternal GDM was a risk factor for offspring elevated BP, and our study is in line with those showed a positive association of GDM with childhood increased BP. 8,28 We found the HBP risks in non-GDM group was 12.2%, which was similar to a prevalence of 12.8% in 5381 Portuguese children and adolescents measured by single visit. 29 The HBP risks in GDM group was 17.4% (male: 22.6%, female: 12.9%), which was also comparable to Marion et al's study.…”
Section: Discussionsupporting
confidence: 78%
“…Complete data on offspring SBP were available from 20 studies [ 18 , 21 , 31 39 , 41 44 , 46 – 48 , 50 , 51 ] and on DBP from 18 studies [ 18 , 21 , 31 39 , 41 , 42 , 44 , 46 – 48 , 50 ]. In addition, one of the included studies [ 36 ] had two cohorts and the other one [ 42 ] included three. Apart from the data on GDM and offspring BP, authors provided separate data for T1DM in five original studies [ 39 , 41 , 44 , 46 , 50 ] and T2DM in one study [ 32 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…17 studies were conducted on high-income countries (HICs) which accounted for the majority of participants (73.9%). Three (13.0%) studies [ 18 , 33 , 36 ] were conducted in upper-middle-income countries (UMICs), and the remaining three (7.4%) studies [ 32 , 37 , 38 ] were in lower-middle-income countries (LMICs). A description of all studies’ characteristics was provided in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations